EAST evidence-based statement on "Stand Your Ground" laws. Issue 3 (10th September 2022) - Kaufman, Elinore J.; Zakrison, Tanya L.; Hoofnagle, Mark H.; Tatebe, Leah C.; Rattan, Rishi; Murphy, Patrick B.; Smith, Randi N.; Joseph, D'Andrea K.; Yeh, D. Dante; Haut, Elliott R.; Como, John J.; Christmas, A. Britton; et al.
Abstract : EAST finds that "Stand Your Ground" laws increase homicide and inequity. Trauma surgeons must play a role in addressing structural causes of violence.